2021
DOI: 10.1136/neurintsurg-2020-017102
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity transvenous access for neuroendovascular procedures: an international multicenter case series

Abstract: BackgroundRadial artery access for transarterial procedures has gained recent traction in neurointerventional due to decreased patient morbidity, technical feasibility, and improved patient satisfaction. Upper extremity transvenous access (UETV) has recently emerged as an alternative strategy for the neurointerventionalist, but data are limited. Our objective was to quantify the use of UETV access in neurointerventions and to measure failure and complication rates.MethodsAn international multicenter retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The authors present the cases of two patients undergoing combined TRA and UETV for CCF embolization. UETV has been well-explored in interventional cardiology literature, but there are few studies in the neurointerventional literature, as UETV is still an emerging strategy in the field [1]. Combined arterial and venous access in the arm has gained additional traction in interventional cardiology due to the possibility of patients continuing anticoagulation and thereby avoiding thromboembolic events that might occur when anticoagulation is held, which is particularly relevant in cardiac patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors present the cases of two patients undergoing combined TRA and UETV for CCF embolization. UETV has been well-explored in interventional cardiology literature, but there are few studies in the neurointerventional literature, as UETV is still an emerging strategy in the field [1]. Combined arterial and venous access in the arm has gained additional traction in interventional cardiology due to the possibility of patients continuing anticoagulation and thereby avoiding thromboembolic events that might occur when anticoagulation is held, which is particularly relevant in cardiac patients.…”
Section: Discussionmentioning
confidence: 99%
“…There was a 9% failure rate using upper extremity TVA due to small venous size, occlusion, or inability to access [7]. Another prospective study on 1007 patients analyzed arm and femoral access for cardiac procedures and found shorter procedure duration and fluoroscopy time, with lower radiation doses and rates of hematoma in the arm group [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other uncommon but serious adverse events in transfemoral or transjugular venous approaches include pneumothorax, hematoma formation compromising the airway, and plexus injury, all of which can be avoided if performing a superficial upper limb veins access. 11 In a multicenter case series by Abecassis et al 15 , patients who underwent superficial upper limb veins for neuro-interventional procedures had no adverse complications, with only 3.4% of the patients requiring conversion to the transfemoral venous approach.…”
Section: D E F a Bmentioning
confidence: 98%
“…Advanced cone-beam computed tomography venous imaging is helpful. 20 Although not used in this series, other points of venous access (eg, upper extremity 21 and direct internal jugular puncture 22 ) may shorten the distance needed to access a fistula and avoid traversal of the right atrium. As has been used for transvenous arteriovenous malformation embolization 23 in this series, 24 placing an arterial balloon can assist in venous retrograde navigation and help protect against retrograde embolization with liquid embolics.…”
Section: Technical Nuancesmentioning
confidence: 99%